A rapid and quantitative method for the analysis of cell migration using retroreflective Janus particular probe and micropatterned surface - 양은경 (The Graduate School, Ajou University, 2024)
Cell migration is a fundamental process that plays a crucial role in various physiological and pathological events. By understanding the factors influencing cell migration, we can advance scientific knowledge and develop potential therapeutic interventions. Consequently, there is a growing demand for reliable and versatile cell migration assays that can be used for in vitro analysis. The scratch wound healing and Transwell assays are conventional methods for studying cell migration. However, they have limitations such as manual wound creation and the inability to track individual cell movements in real-time. Herein, we developed a novel assay that combines the advantages of these methods. This assay utilizes a micropatterned plate, eliminating the need for manual scratches and incorporating a retroreflection optical analysis system for precise cell tracking. By introducing a retroreflective system with micro-scale mirror particles, we achieved real-time cell migration tracking with minimal interference from the surrounding environment. The assay performance was evaluated using L929 fibroblasts treated with cyclic Arg-Gly-Asp as a migratory control molecule, and the degree of cell migration was quantified by analyzing the positional change of retroreflective signals. The results demonstrated the feasibility of the developed assay for analyzing cell migration. This novel method provides a tool for quantitative and controlled cell migration analysis, facilitating further research and potential therapeutic interventions.
학위논문(석사)--분자과학기술학과,2024. 2
Keywords: Cell migration